2012
DOI: 10.1016/j.ijgo.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quality of life following spontaneous conception and assisted reproduction

Abstract: The results underline the higher burden that pregnancy represents for women on a physical and social level. ART treatment seems to increase the negative impact of pregnancy on QoL in the couple as a whole; early support in adjusting to the realities and demands of pregnancy might prove beneficial for these future parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
1
12
0
2
Order By: Relevance
“…In contrast, some studies, such as the study by Paskalez et al, show that infertile women and couples who have used infertility treatment techniques have lower quality of life levels (Pascalis, Agostini, Monti, Paterlini, Fagandini, & La Sala, 2012). Hassanian's study shows that infertility is the cause of lower quality of life score in women with primary infertility.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…In contrast, some studies, such as the study by Paskalez et al, show that infertile women and couples who have used infertility treatment techniques have lower quality of life levels (Pascalis, Agostini, Monti, Paterlini, Fagandini, & La Sala, 2012). Hassanian's study shows that infertility is the cause of lower quality of life score in women with primary infertility.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…, De Pascalis et al . ). In this study, HRQoL was assessed using the Taiwanese version of the SF‐36 (Lu et al .…”
Section: The Studymentioning
confidence: 97%
“…, De Pascalis et al . ). However, obstetric factors that predict HRQoL have not yet been fully examined.…”
Section: Introductionmentioning
confidence: 97%
“…In this sense, the levels of body perception of infertile women whose only purpose is to become pregnant and have a healthy baby in case of pregnancy are a matter of curiosity. Although the literature reports that women using assisted reproductive methods may have different needs in pregnancy than fertile women, the information on this issue is insufficient . Additionally, no study was found to investigate the body perceptions of women who become pregnant after using assisted reproduction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature reports that women using assisted reproductive methods may have different needs in pregnancy than fertile women, the information on this issue is insufficient. [13][14][15][16] Additionally, no study was found to investigate the body perceptions of women who become pregnant after using assisted reproduction methods. Therefore, the body perception levels that may be caused by pregnancy as a result of using in vitro fertilization (IVF) in infertile women were compared to those of women who become pregnant spontaneously.…”
Section: Introductionmentioning
confidence: 99%